DO CONHECIMENTO EM SÃO TOMÁS DE AQUINO - PINHEIRO , Ermilton César Sousa (2024)
The present dissertation aims to present the entire process of knowledge in the view of Saint Thomas Aquinas, which begins in sensation and ends in intellect. For him, knowledge is the ability of the intellect to capture the principle of determination of the essence of the being, it is to receive the accidental form that is instantiated in the matter that is captured by the external senses at the first level of human knowledge: sensation. According to Saint Thomas Aquinas (ST. Iª, q.84, a.8 Respondeo) “natural knowledge originates in the senses, we are born without any knowledge, but only with the faculty of knowing, that is, we do not know anything that does not have past them.” Sensitive knowledge is the material of intellective knowledge, the act of understanding, knowing, is not a faculty only of the soul, but also of the body, through the senses. Once information is received from the senses, it is memorized. Two types of knowledge are then formed: sensitive and intellective. This is an essential point that points to Saint Thomas Aquinas' theory of knowledge, which does not, in any way, dispense with the external and internal senses in the process of human intellection. Therefore, for Saint Thomas Aquinas, an adequacy of: senses (faculty of the body) and intellect (faculty of the soul) is necessary. Both are necessary for man so that he can acquire true knowledge, however, the capacity for intellection is contained in the human soul, as its main faculty, with the help of the senses, which are external and internal. This is the subject that this dissertation intends to research, for this, we will take a journey through the entire trajectory that Saint Thomas Aquinas used to formulate his idea about knowledge.